The Effect of Carrier Phase on GPS Multipath Tracking Error - Mubarak, O. M. (Engineering, Technology & Applied Science Research, 2020)
Multipath is one of the main sources of tracking error in GPS receivers. This tracking error has previously been analyzed against the relative delay of the Line Of Sight (LOS) and reflected signals. However, only carrier phase differences of 0 and π were used, since they give tracking error with maximum magnitude. This paper shows that tracking error does not change linearly with changing carrier phase difference. Tracking error plots against relative carrier phase difference of the LOS and reflected signals have been used to analyze the relationship between the two in various scenarios. While maximum positive and negative errors are found at carrier phase difference of 0 and π, a sharp increase in tracking error is found around the phase difference of π. There is a zero crossing in all plots but that point is dependent on relative amplitude, delay, and carrier phase difference of the two signals. The analysis has also been extended to narrow correlators receiver. Tracking error is significantly reduced in this case, however, similar characteristics have been observed when the tracking error is analyzed against the relative carrier phase difference. Moreover, the tracking error was found to be less dependent on the relative delay between the two signals when correlators spacing is reduced.